(untitled) (Research, Society and Development, 2021)
Waste is one of the main causes of increased costs in the production of meals. Thus, the objective was to evaluate waste management and the hygienic-sanitary and microbiological conditions of food and surfaces in a pizzeria in northern Bahia. This is a cross-sectional, qualitative and quantitative study. The hygienic-sanitary diagnosis was carried out through the application of a checklist according to RDC nº 216/2004, ANVISA, and the microbiological analysis performed for the counting of total coliforms, Escherichia coli, Staphylococcus aureus and the presence / absence of Salmonella, in the food samples . For the analysis of surfaces and equipment, the swab technique and the counting of total coliforms and Escherichia coli were used through the Petrifilm Coliform Count Plate 3M® analysis system. Acceptable values ​​of total coliforms were observed on the pizza, tomato and chicken board, with values ​​of 1.40 x 10³ UFC / cm², 1.04 x 10³ UFC / g, 1.70 x 10³ UFC / g, respectively; and unacceptable in the food processor, corresponding to 4.88 x 10³ UFC / cm². It was found 1.3 x 10³ UFC / mL, total coliforms in the water, where it should be absent. There were no Escherichia coli colonies or Salmonella in the samples. As for the hygienic-sanitary conditions, the pizzeria was classified in group 3 (0 to 50% of the items’ service), according to RDC nº 275/2002. Therefore, the presence of a technician in charge of food service is necessary, presenting a direct relationship in the control of waste and hygienic-sanitary, promoting corrective actions that provide the reduction of risks associated with food contamination and optimization of operating costs.